(3JaSjQ GdJMQjQs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3GdSYO bQjf ef UOQ cdGeg HGdMeO dhGgH GdSYGOI hHYO , aef GdeYdhe Cf cJGH GdeLSWi GdefShH Edi HWdjehS GdbhPi cJGH TgO dg GdYGdehf ai ENJQGYg HGdbOM GdeYdi s
(3BNQgG (B:s
(3hdSJ CdJeS HgPG GdOYGA EfHGJ gPg GdCTjGA dhRjQ GdhRQGA aGdJeGS Pdc jchf JMUjdkG ddMGUd Hd GdedJeS efg JYGdi Gf jfYe Ydjg dMXI HdMXI s
(3HgG fXGe GdJYbjHIs
(3HgG QShe hCTcGd gfOSjIs
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi s
(3HGNJdGa ai HYV GdCdaGX s
(3cJHJ Yf fSNI cJHJ SfI (B888(3g` bhHdJ Ydi fSNI HNW GdeDda s
Keywords: (3Gdadcs